R&D Speaks Rural & Small Schools. - Southwest Educational Development Lab., Austin, TX.; Southwest Educational Development Lab., Austin, TX. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
The goals of a rural and small schools conference held in December, 1980 in Austin, Texas are to link the region's educators who are concerned with rural and small schools at both state and local levels with current research and resources and to identify needs of rural and small schools in the region (Arkansas, Louisiana, Mississippi, New Mexico, Oklahoma, and Texas). Included are the following: "Rural Education: A Description and Challenge" (D. Carmichael); "The History of Rural & Small Schools" (E. Edington); "A Profound Transformation" (AASA slide/tape); "Developing a Rural Policy" (A. Cosby); "Achievement, Curriculum, Staffing, and Barriers to Innovation & Change" (E. Edington); "Small School Districts: Barriers to Equal Opportunities for Students?" (J. Veselka); "A State Service Center Delivery Model: Regional Education Service Centers in Texas" (T. Lawrence); "Texas' Project CITE: An Information Resource for the Region" (J. Anderson); "Special Education Training for Rural Areas" (J. Evans). Also included are comments on common misconceptions of the word "rural" and four specific recommendations for rural education: don't design rural schools using urban models; train teachers to teach in rural areas; encourage the development of rural curricula; and explore varied service delivery models for equalizing opportunity. Appendices are included. (AN)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: 400-80-0107.
ERIC Note: Paper copy not available due to publisher's choice.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement; Ancillary School Services; Definitions; Demography; Education Service Centers; Educational History; Educational Innovation; Educational Needs; Educational Policy; Equal Education; Faculty; Information Dissemination; Rural Education; Rural Schools; Small Schools; Special Education; Teacher Education; Collected Works, Proceedings